2017
DOI: 10.1111/1742-6723.12841
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ choice between public and private hospital emergency departments: a cross‐sectional survey

Abstract: Longer waiting times in public EDs is the principal issue considered by patients choosing private EDs and the out-of-pocket payment for accessing private EDs is the principal issue considered by public ED patients. The study suggests that addressing the out-of-pocket payments will attract more patients with private health insurance to access private EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(13 reference statements)
1
2
0
Order By: Relevance
“…However, the education variable, which was mostly higher, reflects the characteristics of the patients of this hospital. These findings show that patients who have access to private medical care have higher socioeconomic status, sometimes determined by having higher levels of education, thus corroborating an Australian study showing that patients usually visit EDs in private hospitals when they have higher purchasing power (24) . Regarding the medical specialty variable, the findings show that most patients seek care for their clinical complaints.…”
Section: Discussionsupporting
confidence: 80%
“…However, the education variable, which was mostly higher, reflects the characteristics of the patients of this hospital. These findings show that patients who have access to private medical care have higher socioeconomic status, sometimes determined by having higher levels of education, thus corroborating an Australian study showing that patients usually visit EDs in private hospitals when they have higher purchasing power (24) . Regarding the medical specialty variable, the findings show that most patients seek care for their clinical complaints.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore using a five-likert scale the study investigated the perception of the patients on the factors for choice of healthcare delivery at public hospitals. By focusing on health provider characteristics the results show that the patients strongly agreed and agree on treatment cost [16] and [23][24][25] distance from the hospital [23] and [25][26][27], location of the hospital [23] and medicine availability [23][24] as the key indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Pongsupap and Lerberghe believed that the drug cost of private medical institutions was at least twice that of public medical institutions [7]. Private medical institutions faced the obstacle of patient out-of-pocket costs [8]. Overall, previous research has shown differences in health costs between public and private medical institutions.…”
Section: Introductionmentioning
confidence: 99%